Impact of MOSFET gate-oxide reliability on CMOS operational amplifiers in a 130-nm low-voltage CMOS process - Chen, JS; Ker, MD (My University, 2005)
The effects of the gate-oxide reliability of MOSFETs on operational amplifiers were investigated with the two-stage and folded-cascode structures in a 130-nm low-voltage CMOS process. The tested operating conditions include unity-gain buffer (close-loop configuration) and comparator (open-loop configuration) under different input frequencies and signals. After overstress, the small-signal parameters, such as small-signal gain, unity-gain frequency, and phase margin, were measured to verify the impact of gate-oxide reliability on circuit performances of the operational amplifier. The gate-oxide reliability can be improved by the stacked configuration in the operational amplifier with folded-cascode structure. A simple equivalent device model of gate-oxide reliability for CMOS devices in analog circuits was investigated and simulated.